(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The growing presence of social media in the lives of families with children affected by incurable illnesses raises significant cultural and ethical concerns. While digital storytelling can provide emotional support and promote awareness, it also exposes minors to risks related to privacy, identity, and digital profiling. This article explores the delicate balance between visibility and the protection of children’s dignity, examining the role of parents, healthcare professionals, and organizations in shaping these narratives. It also presents the Imago project, which offers clear and non-coercive guidelines to promote responsible sharing practices.